Population age structure: An underlying driver of national, regional and urban economic development - Anders Malmberg; Bo Malmberg; Peter Maskell (ZFW - Advances in Economic Geography, 2023)
This paper argues that population age structure plays a significant role alongside institutional, technological, political, and cultural factors when it comes to explaining shifts in urban, regional and national economic development. The paper demonstrates how demographic transitions lead to changes in population age structure which in turn correlate with global shifts in economic development from 1950 onwards. It then analyzes the role of population age structure at the sub-national level by reviewing some prominent cases of regional and urban shifts in Western Europe and North America. Population size, population density and migration have always been an integrated part of economic geography, and the consequences of ageing in national and regional economies are increasingly being studied. The specific role of population age structure as a driver of economic development has, however, so far largely been ignored in the field.
https://doi.org/10.1515/zfw-2023-0041
Keywords: 330; age structure; aging; demography; Economic Growth; Regional shifts; Working age ratio